Carbon Monoxide Induced Metabolic Shift in the Carboxydotrophic Parageobacillus thermoglucosidasius DSM 6285 - Habibu Aliyu; Ronnie Kastner; Pieter de Maayer; Anke Neumann (Microorganisms, 2021)
Parageobacillus thermoglucosidasius is known to catalyse the biological water gas shift (WGS) reaction, a pathway that serves as a source of alternative energy and carbon to a wide variety of bacteria. Despite increasing interest in this bacterium due to its ability to produce biological hydrogen through carbon monoxide (CO) oxidation, there are no data on the effect of toxic CO gas on its physiology. Due to its general requirement of O2, the organism is often grown aerobically to generate biomass. Here, we show that carbon monoxide (CO) induces metabolic changes linked to distortion of redox balance, evidenced by increased accumulation of organic acids such as acetate and lactate. This suggests that P. thermoglucosidasius survives by expressing several alternative pathways, including conversion of pyruvate to lactate, which balances reducing equivalents (oxidation of NADH to NAD+), and acetyl-CoA to acetate, which directly generates energy, while CO is binding terminal oxidases. The data also revealed clearly that P. thermoglucosidasius gained energy and grew during the WGS reaction. Combined, the data provide critical information essential for further development of the biotechnological potential of P. thermoglucosidasius.